Inhibition of CXCR4/CXCL12 signaling axis by ursolic acid leads to suppression of metastasis in transgenic adenocarcinoma of mouse prostate model - Shanmugam, M.; Manu, K.; Ong, T.; Ramachandran, L.; Surana, R.; Bist, P.; Lim, L.; Kumar, Alan Prem; Hui, K.; Sethi, G. (2011)
Increasing evidences indicate that CXCR4/CXCL12 signaling pathway plays a pivotal role in the process of distant site metastasis that accounts for more than 90% of prostate cancer related deaths in patients. Thus, novel drugs that can downregulate CXCR4/CXCL12 axis have a great potential in the treatment of metastatic prostate cancer. In this report, we tested an agent, ursolic acid (UA) for its ability to modulate CXCR4 expression in prostate cancer cell lines and inhibit metastasis in vivo in transgenic adenocarcinoma of mouse prostate (TRAMP) model. We observed that UA downregulated the expression of CXCR4 in prostate cancer cells irrespective of their HER2 status in a dose- and time-dependent manner. Neither proteasome inhibitor nor lysosomal stabilization had any effect on UA-induced decrease in CXCR4 expression. When investigated for the molecular mechanisms, it was observed that the downregulation of CXCR4 was due to transcriptional regulation as indicated by downregulation of mRNA expression, inhibition of NF-?B activation and modulation of chromatin immunoprecipitation activity. Suppression of CXCR4 expression by UA further correlated with the inhibition of CXCL12-induced migration and invasion in prostate cancer cells. Finally, we also found that UA treatment can inhibit metastasis of prostate cancer to distal organs, including lung and liver and suppress CXCR4 expression levels in the prostate tissues of TRAMP mice. Overall, our experimental findings suggest that UA exerts its antimetastatic effects through the suppression of CXCR4 expression in prostate cancer both in vitro and in vivo. Copyright © 2011 UICC.